Why do our Theories Matter? - Rick Shearer (Flexible Learning Association of New Zealand, 2021)
All too often in our practice of distance education we overlook the history of the field and our theories as we embrace new technologies or, as in the past year, when we are forced to adapt to a regional or global crisis that necessitates a temporary move to a remote learning scenario. When we set our theories aside, this approach can lead us to recreate the wheel in our pedagogical approaches, and ignores the unique pedagogy of distance education and the unique characteristics of learners studying at a distance. This article looks at why our distance education theories continue to be critically important for us to constantly return to and reflect on. Our theories help us to keep focused on the learner, learner characteristics, and the individualised nature of learning, while we undertake design and development work in partnership with faculty and other members of the design team. Our distance education theories remind us to ask the hard questions about what we are trying to accomplish and to what end for the learner, and through which design strategies.